Pencegahan Covid-19 Melalui Sosialisasi dan Pembagian Masker di Pasar Kelurahan Sindang Sari Kota Samarinda - Nurul Hikmah; Euis Kusumarini; Desi Delpriano (Jurnal Pengabdian Masyarakat Formosa, 2022)
The activity "Covid-19 Prevention Through Dissemination and Distribution of Masks at the Sindang Sari Village Market, Samarinda City" generally aims to protect the public from the corona virus. The output of this community service is publication in a national community service journal. Methods of Service Implementation by: 1) The team carried out observations and interviews to find out what the residents needed, 2) The results of the observation phase were then taken into consideration to provide assistance that the community had never received, namely mask assistance, 3) The next stage the team service prepares masks that are needed by the community, 4) At the stage of giving masks, the service team explains or socializes the benefits of using masks and the impact of not using masks.Based on the results of field observations and interviews during a visit to one of the Kelurahan, there are still people who do not comply with wearing masks. The purpose of this service activity is to provide understanding and increase public awareness about the benefits and importance of wearing masks. So that the spread and transmission of COVID-19 can be reduced. The implementation of the community service program in the Sindang Sari Sub-District, Welcome District, Samarinda City, went smoothly as planned